I am trying to understand implicit differentiation; I understand what to do (that is no problem), but why I do it is another story. For example: 3y^2=5x^3

Sara Solomon 2022-10-08 Answered
I am trying to understand implicit differentiation; I understand what to do (that is no problem), but why I do it is another story. For example:
3 y 2 = 5 x 3
I understand that, if I take the derivative with respect to x of both sides of the equation, I'll get:
d d x ( 3 y 2 ) = d d x ( 5 x 3 )
6 y d d x ( y ) = 15 x 2 d d x ( x )
6 y d y d x = 15 x 2 d x d x
6 y d y d x = 15 x 2
d y d x = 15 x 2 6 y
Unless I made some sort of error, this is what I am suppose to do. But why? Specifically, on the second line, I utilize the chain rule for the "outer function" and get 6y, but I still need to utilize the chain rule for the "inner function" which is the y. So why don't I go ahead and take the derivative of y and get 1? I know that I am not suppose to, but I don't really "get it." It seems to me that I only use the chain rule "halfway". Why isn't it an all or nothing? If it's all done with respect to x, it would seem to me that the 3y^2 should remain unchanged entirely. This is my problem.
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Answers (2)

Shane Middleton
Answered 2022-10-09 Author has 7 answers
d y d x may equal 1 in special cases, but it is not generally so. The very point of implicit derivation is that you don't know what it is.

So, the Chain Rule is used to separate the derivative of a function of y wrt x into two differential terms, one you can resolve, and one unknown.

To be clear, here's the process with the stage added and highlighted. Does this help?
3 y 2 = 5 x 3 d ( 3 y 2 ) d x = d ( 5 x 3 ) d x Take the derivative w.r.t.  x d ( 3 y 2 ) d y d y d x = d ( 5 x 3 ) d x Apply the Chain Rule to the L.H.S. 6 y d y d x = 15 x 2 Evaluate the polynomial derivatives  d ( c z n ) d z = c n z n 1 where  n N ,  and  c  is constant d y d x = 5 x 2 2 y Use arthimetic rearrangement
Alternatively, we might use explicit differentiation, as follows:
3 y 2 = 5 x 3 y = x 3 / 2 5 3 d y d x = d x 3 / 2 d x 5 3   = 3 x 1 / 2 5 2 3   = 3 x 1 / 2 5 2 3 × x 3 / 2 5 y 3  re:    = 5 x 2 2 y
Did you like this example?
Subscribe for all access
Sanai Ball
Answered 2022-10-10 Author has 1 answers
Change y to y ( x ) and everything should be clear. y is not a constant, but a function of x.
d y d x = d d x y ( x ) = y ( x )
Did you like this example?
Subscribe for all access

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

You might be interested in

asked 2022-08-15
I understand the method used in implicit differentiation, it's just an application of the chain rule. But why can you define y as a function of x?
In this equation for example:
x 2 + y 2 = 1
2 x + 2 y y = 0
Why isn't it just this?:
2 x + 2 y = 0
Thank you in advance.
asked 2022-10-15
Use implicit differentiation to determine z x in y z = l n ( x + z ) and sin ( x y z ) = x + 2 y + 3 z.
Here is my answer:
y z = l n ( x + z )
y z = ( 1 + z ) 1 x + z
z = 1 y x + y z 1
and
sin ( x y z ) = x + 2 y + 3 z
y ( z + x z ) cos ( x y z ) = 1 + 3 z
y z cos ( x y z ) + x y z cos ( x y z ) = 1 + 3 z
y z cos ( x y z ) 1 = z ( 3 x y cos ( x y z ) )
z = y z cos ( x y z ) 1 3 x y cos ( x y z )
is that right?
asked 2022-08-14
I am trying to solve the problem: x 2 + x y + y 3 = 0 using implicit differentiation.
My workings:
( 1 ) d d x [ x 2 ] + d d x [ x y ] + d d x [ y 3 ] = d d x [ 0 ]
( 2 ) 2 x + y + d y 3 d y d y d x = 0
( 3 ) 2 x + y + 3 y 2 ( d y d x ) = 0
( 4 ) d y d x = 2 x + y 3 y 2
But the answer says it should be:
( 3 ) 2 x + y + d x y d y d y d x + 3 y 2 ( d y d x ) = 0
( 4 ) 2 x + y + d y d x ( x + 3 y 2 ) = 0
( 5 ) d y d x = 2 x + y x + 3 y 2
Why?
asked 2022-08-17
If 4 x 2 + 5 x + x y = 4 and y ( 4 ) = 20, find y ( 4 ) by implicit differentiation.
I implicitly differentiated the equation, but I don't see how I can use y ( 4 ) = 20 to my advantage.
asked 2022-09-27
Consider the curve R 2 given by the equation:
x 2 y 2 = 1
a/ Use the method of implicit differentiation to find all points on the curve at which that tangent has a slope of 5 3
b/ Explain why there are no points on the curve at which the tangent is horizontal.
So far, I have found the implicit differentiation, which is d y d x = x y . Can you guys help me what should I do next. Any help is appreaciate
asked 2022-07-23
I was looking to implicitly differentiate
22 x 6 + 4 x 33 y + y 7 = 17
and found it to be
d y d x = 132 x 5 132 x 32 y 4 x 33 + 7 y 6
Now, I am trying to find the equation of the tangent line to the curve at the coordinate (1,1). So I then plug both 1 in for x and y into the above equation and come up with
0 11
Now I go to solve
y y 1 = m ( x x 1 )
getting
y 1 = 0 ( x 1 )
resulting in y = 1 and the equation to be y = x + 1 for my final answer. Am I going about this in the correct manner?
asked 2022-09-28
An equation is defined as x + y + x 5 y 5 = 0.
a. Show that the equation determines y as a function of x in a neighbourhood of the origin (0,0).
b. Denote the function from ( a ) by y = φ ( x ). Find φ ( 5 ) ( 0 ) and φ ( 2004 ) ( 0 ).
For the first part,I simply needed to prove that the equation is C 1 in the neighbourhood of the origin and that the first derivative w.r.t.y does not vanish at that point. These are the sufficient conditions for the existence of an implicit function in the neighbourhood of the origin.
For the second part, I could do implicit differentiation (in a usual way) had it been for lower orders. But I need to learn the case for higher orders like the question asks. Please give me some hints.

New questions